BASIC AND ASSOCIATED CATEGORIES OF PHYSICAL RECREATION - Elmurzaev, M.A.; Aslakhanov, S.-A.M.; Zinoviev, N.A.; Alekseeva, N.D. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to highlight the basic and related categories of physical recreation. Methods and structure of the study. The methodological basis of the study was carried out on the lines of theoretical and empirical methods based on a comparative analysis of the practice of organizing physical recreation. Results and conclusions. The authors have singled out such basic categories of physical recreation as a subject - an object, motor activity, spatio-temporal conditions of its functioning and the final result achieved. The presented basic categories of physical recreation in varying degrees and meaningful interpretation are indicated in almost all scientific concepts, in various scientific disciplines studying it, and are of a universal nature. Related categories are identified on the basis of the system of knowledge accumulated in related scientific disciplines. The authors include such accompanying categories: social recreation, biological recreation, recreational geography, ecological recreation, cultural recreation, resort and sanatorium recreation and many others. The allocation of related categories in scientific research occurs on the basis of taking into account specific areas of application of physical recreation in human life. The selected basic and accompanying categories form a single recreational system in which they are represented in close interaction and interrelation.